The Viability And Vigor Of Rice Varieties (Oryza Sativa L. ) Under High Temperature - Afrima Sari; Aswaldi Anwar; Nalwida Rozen (JERAMI : Indonesian Journal of Crop Science, 2019)
The growth and initial development of the plant greatly determines the survival of the plant at the next stage. This initial phase is also the most sensitive phase of abiotic stress. The level of viability and vigor to produce normal sprouts can explain the success of germination. The aim of this research is to study the temperature change to viabilily and vigor in four rice varieties. Research started from January to February 2018 at Seed Technology and Plant Physiology Laboratory Andalas University and Chemistry Laboratory University Of Padang. This research applies Factorial Experiment in Completely Random Design, where the first factor is four levels of rice varieties, Anak Daro, Batang Piaman, Cisokan and Inpari 30. The second factor is temperature level, 28 0C, 32 0C, 36 0C, 40 0C, 44 0C and 48 0C. Viability and vigor decrease when temperature increase. The optimum temperature for rice germination is 28-32 0 C for Anak Daro, 28-36 0 C for Cisokan, at 28 0 C for Batang Piaman and Inpari 30. Anak Daro and Inpari 30 can germinate until 40 0C. The highest vigor index value at 28 0 C in Cisokan and Inpari 30 (89,33 %). At 28-32 0C Cisokan, Batang Piaman and Inpari 30 has been able to germinate on the second day after planting, but Anak Daro can normal germinate on the third day after planting.